Perbedaan komunikasi antar kebudayaan yang berbeda - Innaka Fhatarani Batubara (JRTI (Jurnal Riset Tindakan Indonesia), 2017)
intercultural communication in Indonesia is very important because in reality the life of society and culture of Indonesia is very heterogeneous consisting of various tribes, language, religion, race, culture, and custom.